The Use of Sentences with one Verb in an Elegant Literary Style - Allaniyazova, Sharigúl; Maksetova, Nilufar (European Journal of Life Safety and Stability (2660-9630), 2023)
One of the styles that have a distinct place in the system of functional styles is the literary style or the language of literary literature. A distinctive feature of this style is the wide range of language materials that can be covered in the style of beautiful literature, the existence of existing lexical associations in the language of the entire population, and the provision of elements of styles to serve the mnemonic task. The reason is that this possibility is limited in other styles.